Facile Chemical Processing of Geloina coaxans Shell and Sodium dihydrogen Phosphate as Precursors to Produce Hydroxyapatite - Pepi Helza Yanti; Resti Resmalina (Jurnal Kimia Valensi, 2020)
This paper reports the synthesis of hydroxyapatite from Geloina coaxans shell and sodium dihydrogen phosphate as precursors by facile and simple method. Firstly, Geloina coaxans shell calcined at 1000 oC for 12 hours to produce lime or CaO. The chemical composition of Geloina coaxans shell calcined was analyzed using the XRF technique, and the result shows that the main component of Geloina coaxans shell calcined was calcium. Synthesis of hydroxyapatite has been done with stirring and aging time parameters and molar ratio of precursors was 1.67.  The XRD patterns showed a specific peak of hydroxyapatite that appeared at 2θ=31.8 o and based on the XRD results on the aging time indicated that the rate of growth of HAp crystals was better and faster at aging for 12 hours. The crystal size of HAp obtained was 37 nm. The FTIR spectra of hydroxyapatite showed characteristics of hydroxyl and phosphate bands in sample spectra. The morphology of hydroxyapatite synthesized also was examined by SEM and the results showed spherical morphology.